Effect of a scoring system and protocol for sedation on duration of patients' need for ventilator support in a surgical intensive care unit. Issue 3 (2nd June 2004) - Brattebø, G; Hofoss, D; Flaatten, H; Muri, A K; Gjerde, S; Plsek, P E
Abstract : Problem: Need for improved sedation strategy for adults receiving ventilator support. Design: Observational study of effect of introduction of guidelines to improve the doctors' and nurses' performance. The project was a prospective improvement and was part of a national quality improvement collaborative. Background and setting: A general mixed surgical intensive care unit in a university hospital; all doctors and nurses in the unit; all adult patients (>18 years) treated by intermittent positive pressure ventilation for more than 24 hours. Key measures for improvement: Reduction in patients' mean time on a ventilator and length of stay in intensive care over a period of 11 months; anonymous reporting of critical incidents; staff perceptions of ease and of consequences of changes. Strategies for change: Multiple measures (protocol development, educational presentations, written guidelines, posters, flyers, emails, personal discussions, and continuous feedback) were tested, rapidly assessed, and adopted if beneficial. Effects of change: Mean ventilator time decreased by 2.1 days (95% confidence interval 0.7 to 3.6 days) from 7.4 days before intervention to 5.3 days after. Mean stay decreased by 1.0 day (−0.9 to 2.9 days) from 9.3 days to 8.3 days. No accidental extubations or other incidents were identified. Lessons learnt: Relatively simple changes in sedation practice had significant effects on length of ventilator support. The change process was well received by the staff and increased their interest in identifying other areas for improvement.